2022
DOI: 10.1002/adfm.202209019
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelet‐Targeted IR780 Immunoliposomes for Photothermal Thrombolysis

Abstract: Acute thrombosis is a leading cause of mortality and morbidity worldwide. Pharmacological thrombolysis relies on plasminogen activators (PAs), which are associated with major side effects including potentially fatal bleeding. Alternative therapeutic options that do not rely on PAs are urgently required. Here, the efficacy of targeted photothermal therapy is evaluated for thrombolysis using liposomes loaded with IR780 dye, which release heat upon near‐infrared (NIR) irradiation. Liposomes targeted to activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The tumor growth is efficiently curbed with the inhibition rate of 97% and eliminated with no recurrence for 30 days. As a result, PTT and its combinational therapies with demonstrated efficacy have been well developed as promising treatment options for various life-threatening diseases. ,, …”
Section: Applicationsmentioning
confidence: 99%
“…The tumor growth is efficiently curbed with the inhibition rate of 97% and eliminated with no recurrence for 30 days. As a result, PTT and its combinational therapies with demonstrated efficacy have been well developed as promising treatment options for various life-threatening diseases. ,, …”
Section: Applicationsmentioning
confidence: 99%
“…These remarkable properties made M1 NPs a promising candidate for PA and fluorescence imaging‐guided PTT in tumor treatment (Figure 2c) (Li, Pang, et al, 2023). Similarly, Wang et al reported the encapsulation of IR780 using 1,2‐dipalmitoyl‐sn‐glycero‐3‐phosphocholine (DPPC), effectively preventing IR780 degradation by oxygen or ROS (Refaat et al, 2023). This encapsulation significantly improved the heating capability of IR780 both in vitro and in vivo, presenting a more effective option for thrombosis treatment.…”
Section: Application Of Dye Aggregates For Enhanced Pttmentioning
confidence: 99%
“…IR780, one of the heptamethine cyanine dyes, has been identified as a promising photoresponsive molecule for cancer photodynamic therapy (PDT) due to minimal scattering and deep-tissue penetration. , However, IR780 has several inherent shortcomings, such as poor solubility in biological fluids, rapid blood clearance rate, and toxicity at large doses, all severely restricting its utility in the clinic . As a result, developing IR780 derivatives for tumor suppression became an important research area. , Additionally, the functions of IR780 derivatives in antitumor bioenergetic therapy has not been thoroughly explored, especially with the emphasis on the positive synergy between mitochondrial metabolism and glycolysis deprivation.…”
Section: Introductionmentioning
confidence: 99%